Determinan Factors of Chronic Energy Deficiency in Pregnant Women - Sulviana; Silfia, Niluh Nita; Usman, Hastuti; Hadina, Hadina; Kusika, Sri Yanti; Pani, Widya; Taqwin, Taqwin (Napande: Jurnal Bidan, 2025)
Background: Chronic Energy Deficiency (CED) in pregnant women is a nutritional problem that impacts the health of both the mother and the fetus. In the working area of Lere Health Center, Palu City, 38 cases of CED were recorded in 2021–2022. This study aims to identify the determining factors of CED occurrence in pregnant women in that area. Method: The research method used was a case-control study with a retrospective approach. The study population consisted of 214 pregnant women, with a sample of 76 respondents selected through purposive sampling. Secondary data were analyzed univariately and bivariately using the Chi-square test through SPSS software. Result: The research results indicate that pregnant women with primary and secondary education levels (65.8%), parity >3, and a history of hyperemesis gravidarum (55.2%) are more likely to experience chronic energy deficiency (CED). Bivariate analysis showed a significant relationship between education (p = 0.000; OR = 9.436), parity (p = 0.000; OR = 6.321), and hyperemesis gravidarum (p = 0.001; OR = 11.998) with the incidence of CED. Conclusion: The conclusion of this study is that there is a relationship between education, parity, and a history of hyperemesis gravidarum with the occurrence of CED in pregnant women. The researchers recommend improving the quality of health services and nutritional counseling to reduce the incidence of CED in the working area of Lere Community Health Center.